The art of happiness a handbook for living - Lama, Dalai (London Hodder and Stoughton, 1998)
The Art of Happiness is a highly accessible guide for a western audience, combining the Dalai Lama's eastern spiritual tradition with Dr Howard C. Cutler's western perspective. Covering all key areas of human experience, they apply the principles of Tibetan Buddhism to everyday problems and reveal how one can find balance and complete spiritual and mental freedom.
Keywords: Religious life--Buddhism.